2022
DOI: 10.3390/ijerph19052506
|View full text |Cite
|
Sign up to set email alerts
|

Recent Climatology (1991–2020) and Trends in Local Warm and Cold Season Extreme Temperature Days and Nights in Arabia

Abstract: The Arabian Peninsula (Arabia) is among the places to have experienced the greatest amount of warming during recent decades, and this trend is projected to continue. Specifics related to the characteristics (frequency, duration, and intensity) of extreme temperature events (ETEs) over Arabia as a whole are either largely outdated or limited only to specific areas. The seasonal ETE definitions commonly used in local studies are neither climatological- nor phenomenon-based. Using a novel and straightforward fram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…However, days that comprise the h‐index can occur during the early and/or late warm season months, which indicates that the h‐index incorporates some of the day‐to‐day thermal variability. Warm events over the Arabian Peninsula tend to occur early (May) and end early (end of July) along the south and east coasts and in highland areas (Alghamdi, 2022). The h‐index analysis was able to detect this pattern, indicating that the h‐index can reflect both spatial and temporal differences (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, days that comprise the h‐index can occur during the early and/or late warm season months, which indicates that the h‐index incorporates some of the day‐to‐day thermal variability. Warm events over the Arabian Peninsula tend to occur early (May) and end early (end of July) along the south and east coasts and in highland areas (Alghamdi, 2022). The h‐index analysis was able to detect this pattern, indicating that the h‐index can reflect both spatial and temporal differences (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…The h-index analysis was able to detect this pattern, indicating that the h-index can reflect both spatial and temporal differences (Figure 3). For example, (Alghamdi, 2022) showed that hot day and night events at Salalah station (ID 30), Oman, on the Arabian Sea coast do not occur in Jul-Sep due to monsoon season. The h-index analysis revealed a similar pattern as hottest days/nights were less frequent or do not occur during monsoon months (Figure 3).…”
Section: Evaluating the H-indexmentioning
confidence: 99%
“…Its central location establishes it as a crucial connectivity area of strategic importance within the country. The city is characterized by an arid climate typical of desert environments, experiencing extreme temperatures that range from hot summers to cold winters [31]. Precipitation is scarce, with an annual average rainfall of only 97 mm, rendering flood events in the region unpredictable due to the erratic nature of rainfall.…”
Section: Description Of the Study Areamentioning
confidence: 99%